Rethinking Achievement Motivation in Indonesian Students: The Influence of Teacher and Peer Relationships Amid a Shifting Collectivist Culture - Efendy, Mamang; Murwani, Danardana; Hitipeuw, Imanuel; Rahmawati, Hetti (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
Despite extensive research on achievement motivation, few studies have integrated the role of students' social relationships—particularly with teachers and peers—within the broader cultural context, especially in collectivist societies. This study addresses that gap by examining whether teacher-student and peer relationships predict achievement motivation and whether collectivist cultural values moderate these associations among Indonesian junior high school students. A total of 317 participants completed standardized questionnaires measuring relationship quality, collectivist orientation, and achievement motivation. Data were analyzed using multiple regression and moderation analysis based on the F. Hayes method. The findings confirmed that both teacher-student and peer relationships significantly predict achievement motivation. However, a novel and unexpected result emerged: collectivist culture did not significantly moderate these relationships. This challenges prevailing theoretical assumptions that collectivist values amplify social influences on motivation and suggests a cultural shift among Generation Z Indonesian students toward more individualistic orientations. These results contribute new insights to motivation research by questioning the continued salience of collectivist values in shaping achievement motivation within modern, digital-age cohorts. The study offers theoretical implications for cross-cultural psychology and practical recommendations for fostering student motivation in evolving cultural contexts.